2021
DOI: 10.7554/elife.67312
|View full text |Cite
|
Sign up to set email alerts
|

YAP and TAZ are transcriptional co-activators of AP-1 proteins and STAT3 during breast cellular transformation

Abstract: The YAP and TAZ paralogs are transcriptional co-activators recruited to target sites by TEAD proteins. Here, we show that YAP and TAZ are also recruited by JUNB (a member of the AP-1 family) and STAT3, key transcription factors that mediate an epigenetic switch linking inflammation to cellular transformation. YAP and TAZ directly interact with JUNB and STAT3 via a WW domain important for transformation, and they stimulate transcriptional activation by AP-1 proteins. JUNB, STAT3, and TEAD co-localize at virtual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 58 publications
2
60
0
Order By: Relevance
“…More recently, a few more studies further identified novel AP-1 co-activators. For instance, the dimeric RACO-1 protein was identified as a c-Jun coactivator, and both YAP (Yes-associated protein) and TAZ (Transcriptional activator with PDZ domain) proteins as b-Jun co-activators required for transcriptional activation by AP-1 [87,88]. As both YAP and TAZ were recently found to be key mediators of the wound healing and tissue regeneration responses to tissue damage [89], it would prove particularly interesting to determine whether both these proteins are expressed in the hTEC and if their expression is affected by wound healing in this biological model.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a few more studies further identified novel AP-1 co-activators. For instance, the dimeric RACO-1 protein was identified as a c-Jun coactivator, and both YAP (Yes-associated protein) and TAZ (Transcriptional activator with PDZ domain) proteins as b-Jun co-activators required for transcriptional activation by AP-1 [87,88]. As both YAP and TAZ were recently found to be key mediators of the wound healing and tissue regeneration responses to tissue damage [89], it would prove particularly interesting to determine whether both these proteins are expressed in the hTEC and if their expression is affected by wound healing in this biological model.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the intact Yki, this fragment retains the ability to be phosphorylated by Wts, suggesting that this is independent of WW binding to Wts and regulation of Yki phosphorylation [ 79 ]. The WW domain in YAP is, however, essential for its activity in order to drive proliferation in vitro and in vivo [ 79 , 80 ] and can facilitate association between YAP and a variety of transcription factors, such as ERBB4 [ 81 , 82 ], JUNB [ 83 ] and RUNX2 [ 84 ], suggesting a TEAD-independent role for YAP as a transcriptional co-activator. A total of eight isoforms of YAP have been reported [ 85 ], with two major isoform types: YAP1 and YAP2, which contain one and two WW domains respectively [ 81 ].…”
Section: Hippo Pathway Dysregulation In Cancermentioning
confidence: 99%
“…These pro-proliferative transcriptional programs may be driven in part by YAP/TAZ–TEAD association with the cell cycle transcription factor complex, AP-1. In a variety of cancer cell lines, YAP, TAZ and TEAD are found to colocalise with AP-1 to regulatory elements of the genome and are necessary for AP-1-mediated expression of cell cycle transcriptional programs, driving cancer cell proliferation and tumorigenesis in in vivo xenograft models [ 83 , 125 , 126 ]. Hyperactive YAP/TAZ also provides cells with a metabolic competitive advantage under nutrient-limiting conditions, in part by up-regulating glucose and high-affinity amino acid transporters [ 127–129 ].…”
Section: Hippo Pathway Dysregulation In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cellular transformation depends on transcriptional co-activators that are key components of signal transduction pathways and are recruited to target sites by DNA-binding proteins. Such co-activators include the YAP and TAZ paralogues, the ultimate targets of the Hippo signaling pathway [ 6 ], and the calcium-binding cytokines S100A8 and S100A9 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%